PENINGKATAN NILAI GUNA SAMPAH PLASTIK NON EKONOMIS SEBAGAI BAHAN DASAR PEMBUATAN PAVING BLOCK DI TPS3R DESA TELUKJAMBE - Kusuma, Anis Mustaghfirin; Bunga, Venny Ulya; Huda, Syamsul; Pambudi, Teguh; Masruroh, Putri; Umam, Hilman Imadul (Universitas Mataram, 2025)
Telukjambe Village as an industrial buffer area faces complex waste management problems where only 29% of 1200 tons of daily waste in Karawang is transported to the landfill. This condition causes accumulation of non-economic plastic waste at TPS3R which remains unoptimized and potentially pollutes the environment. This community service activity aims to improve the knowledge and skills of TPS3R operators in processing non-economic plastic waste into paving blocks. The implementation methods include field observation and literature study to identify partner needs. Furthermore, demonstration workshops and hands-on practice of paving block production were conducted with evaluation using pre-test/post-test and N-Gain analysis. The results showed a 74.4% participant participation rate in all practical stages. There was a 26.67% increase in knowledge measured through pre-test and post-test. N-Gain analysis showed 33.3% of participants experienced very significant improvement and 66.7% showed fairly significant improvement. Participant enthusiasm was also very high during the practical sessions as seen from active engagement in discussions. The conclusion indicates that this activity successfully enhanced the capacity of TPS3R operators in processing non-economic plastic waste into economically valuable products. This success is marked by the achievement of knowledge improvement and active participation of participants.